Performance study of a sustainable solar heating system based on a copper coil water to air heat exchanger for greenhouse heating. (15th January 2022) - Ihoume, I.; Tadili, R.; Arbaoui, N.; Bazgaou, A.; Idrissi, A.; Benchrifa, M.; Fatnassi, H.
Highlights: Performance evaluation of greenhouse heating system based on a copper coil heat exchanger. Significant improvement of the microclimate under the heated greenhouse. Estimation of the volume of heat transfer fluid required for greenhouse heating needs. Optimization of the heating system and. C O 2 m i t i g a t i o n . Abstract: Solar energy plays an important role in addressing greenhouse gas emissions in the agricultural sector. In this context, this paper studies the performance of a solar copper coil heating system used to heat a south-oriented greenhouse. This system relies on the circulation of a heat transfer fluid (water) in a closed loop placed in the greenhouse's roof to store heat during the day, which is then released back into the greenhouse at night. An experimental comparative study was conducted in two identical greenhouses. The first one is equipped with the heating system and the second one is not. The heat balance of the first greenhouse was used to calculate the water mass needed to heat the greenhouse during the night. Comparing the greenhouses microclimate indicated that the nighttime temperature inside the heated greenhouse is 4 °C higher compared to the control one. In the heated greenhouse, the relative humidity is 14% lower on average at night. According to the parametric study, the heat transfer fluid requires 527 L of water to sustain the temperature. The results of the sensibility study on the impacts of varying the air temperature setpoint water volume, provide useful information on how to optimize the heating system and estimate the amount of water flowing through the copper coil heat exchanger. This sustainable heating system has a payback period less than two years. It also has a low environmental impact, with a CO2 emission rate of 176 g/day compared to 41000 g/day for a heating boiler.